Prediction and measurement of high frequency radio frequencies in peninsular Malaysia and comparisons with the international reference ionosphere model - Malik, R. A (American Scientific Publishers, 2017)
Prediction of High Frequency (HF) radio frequency is important in the planning and operation of HF radio system because of the highly variable ionospheric region. Therefore, there is a requirement to find reliable and accurate HF operating frequencies in the Malaysian environment. The main aim of this study was to observe and analyze the HF prediction and measurement in Peninsular Malaysia which was then compared to the IRI Model prediction. This study was carried out in the equatorial region and in the middle of solar cycle 24 which was in July and August of 2014. The HF prediction process involved two maximum usable frequency (MUF) models, and the predicted result, i.e., operating working frequency (OWF) was based on hourly monthly median values. The results show that the IRI Model overestimated MUF prediction at about 36% for July 2014 and 38% for August 2014. This indicates that the IRI Model is an inappropriate model to be used for prediction of HF operating frequency in the Malaysian region. Meanwhile, the OWF measurements were around the OWF prediction, and this indicates that the OWF measurements are in the range of the OWF prediction. Accordingly, the lower decile MUF, i.e., OWF is the right range for HF operating frequency.